What is ‘Western Philosophy’? - Matyáš Moravec; Peter West (Journal for the History of Analytical Philosophy)
Recent discussions in the history of analytic philosophy have targeted questions about the concept of ‘Analytic Philosophy’ itself. Scholars, such as Glock (2008) and Preston (2004), have argued that ‘Analytic Philosophy’ cannot plausibly be characterised in terms of necessary and sufficient conditions and that other, more pragmatic, approaches must be taken instead. In this paper, we argue that similar questions that have recently emerged about the status of ‘Western Philosophy’ can be informed by these debates in the history of analytic philosophy. Some recent scholars, most notably Platzky Miller (2023) and Cantor (2022), have argued that the concept of ‘Western philosophy’ should be abandoned altogether, due to its incoherence and the role it plays in upholding and perpetuating various exclusionary mechanisms and politically dubious aims. The aim of this paper is to apply the lessons learnt from similar discussions about ‘Analytic Philosophy’ and to build on Platzky Miller’s and Cantor’s innovative proposals. We argue that the term should not be abandoned altogether and that continuing to use it is required for combating exclusions in the history of philosophy.